Citizen Sensing: An Action-Orientated Framework for Citizen Science - Coulson, Saskia; Woods, Mel; , Making Sense EU (Frontiers in Communication, 2021)
Citizen Sensing, a correlative of Citizen Science, employs low-cost sensors to evidence local environmental issues and empowers citizens to use the data they collect. Whilst motivations for participation can vary, communities affected by pollution frequently have changemaking as their goal. Social innovation is crucial to citizen sensing, and research in this area must develop practices that support the citizens who wish to shape their world. Therefore, this paper presents an action-orientated framework which emerges from a two-year pan European project. The authors examine five studies and explore the cross-cutting principles, phases, stakeholders, methods and challenges which form this framework. The authors argue that whilst data collection and data awareness are crucial to the citizen sensing process, there are precursory and subsequent stages which are necessary to equip citizens to address complex environmental challenges. We conclude with recommendations for future practice and the value this has for citizen sensing and citizen science.